Decoupling and EKC in European Union countries: a shiftshare decomposition of air emissions - Lodi, Chiara; Bertarelli, Silvia (European Scientific Journal, ESJ, 2024)
This paper examines the non-linear effect of per capita GDP growth rate, trade openness, and physical and human capital endowments on air pollution in the EU region over the period 2008-2016 by decomposing air emissions into scale, composition, and technique effects. Results show a negative non-linear relationship between greenhouse and acidifying gas emissions and per capita GDP growth rate, with more open economies tending to reduce emissions both directly and indirectly through investment in physical capital. The determinants mainly affect the scale component, although the environmental improvement due to capital investment works through the technique component. There are heterogeneous effects across countries, with more pronounced environmental benefits for countries in the higher deciles of GDP and trade growth rates.